TANGGUNG JAWAB PIHAK RETAILTERHADAP PRODUK YANG TELAH KADALUWARSA YANG MENIMBULKAN KERUGIAN PADA KONSUMEN DI KELURAHAN SANUR KOTA DENPASAR - Ari Mertha Sedana, I Wayan; Suardana, I Wayan (Kertha Negara : Journal Ilmu Hukum, 2013)
Consumer protection is every effort that ensures the existence of legalcertaintyto provide protection to consumers . Make it happen with the governmentissued law number 8 of 1999 on the protection of consumers. In it set about the rightsand obligations of consumers and businessmen, also about the responsibility ofbusinessmen. The problem that arises is how retail party responsibility against lossessuffered as a result of consumers to consume products that expire as well as the effortsof what can be done if there is a dispute over consumer losses to consumers as a resultof consuming the product expire?Product liability is a legal responsibility of the agency or produce a product orof the person or entity that is engaged in a process to produce a product or persons orentities who sell or distribute such products. The law of product liability is included inthe Act of breaking the law, but is imbued with strict liability, regardless of whetherthere are errors on the perpetrators. Efforts that can be made consumers if there is adispute over on losses suffered consumers as a result of consume products that areexpired, can be done in two ways, i.e dispute resolution outside the Court and disputeresolution through the courts.
Keywords: Consumer Protection, Responsibility, Legal Certainty, Dispute resolution efforts